Permethrin induced cytotoxicity of rat splenocytes: Protective effect of N-acetylcysteine (Indian Journal of Experimental Biology (IJEB), 2020)
The present study was designed to determine the molecular mechanism associated with permethrin induce cytotoxicity. Rat splenocytes were incubated with increasing concentration of permethrin (0-39 ug/ml) for 6 to 24 h. Cytotoxic effect of permethrin was evaluated by MTT assay. To assess the underneath mechanism of cytotoxicity, different biochemical indices of cell death namely Annexin V binding assay, DNA fragmentation, and levels of caspase 3 were analyzed. To evaluate the oxidative stress, glutathione depletion and melondialdehyde levels were analyzed. MTT assay revealed that permethrin induces cytotoxicity in dose-dependent way. In Annexin-V binding assay, above 7.8 µg/ml concentration, significant necrosis of cells was noticed and consistent with DNA fragmentation assay. A significant dose and time dependent depletion of cellular glutathione (GSH) and increased MDA levels were observed and consistent with the percentage of cells undergoing apoptosis. Co administration of N-acetycysteine mitigates permethrin- induced apoptosis, showing the role of oxidative stress in apoptosis induction. The present study gives experimental evidence that emphasizing the role of oxidative stress in permethrin-induced cytotoxicity in rat splenocytes in vitro.